Fluência em leitura oral e compreensão em leitura : automaticidade na decodificação para a compreensão leitora - Machado, Alessandra Pereira Gomes (2018)
Oral reading fluency is the ability to extract information from the written word, demonstrating understanding in reading aloud. The reading processes verified in oral reading fluency attend to the automaticity in the decoding of the written word. We assume that decoding processes with automaticity are necessary for reading comprehension. Thus, our objective was to identify the behavior of readers' profiles, in the perspective assumed by Morais (1996). For the assessmentof oral reading fluency, we construct a reading model, considering the theoretical construct in which the automaticity in decoding is treated as a predictor in the construction of the text meaning. This reading approach presupposes the dual-rote reading aloud model (COLTHEART et al, 2001; COLTHEART, 2013), reading comprehension model (PERFETTI et al, 2013; PERFETTI; STAFURA, 2014) and monitoring comprehension reading model (OAKHILL et al, 2005; EFKLIDES, 2008). Based on the reading processes of this model, we measured the three dimensions of oral reading fluency: accuracy, speed and prosody. These three dimensions, taken together, allow us to identify processes of automaticity in decoding that lead to a reading comprehension. To verify comprehension in reading, we constructed a test based on the reference matrix of Portuguese Language and on the proficiency scale of Prova Brasil, using items from this assessment made available in the Plataforma Devolutivas Pedagógicas. The oral reading fluency test was based on the Curriculum-Based Measurement method (DENO, 2003), taking into account the procedures of the analysis of 1 minute of reading aloud of two appropriated texts to the reader's level of education. Participants of this study were 74 students of the 6th grade and 72 of the 9th year of elementary education in two public schools in Sergipe: Colégio Estadual Ministro Petrônio Portela (CEMPP) and Colégio de Aplicação da Universidade Federal deSergipe (Codap / UFS). At the beginning of the 2016 school year, the reading comprehension test was applied collectively for all participating students attending the school, while the reading aloud recording session was performed individually in a controlled ambience. The results of the oral reading fluency test allowed to identify three reading profiles that standards the appropriated behavior patterns to the automaticity, comprehension and monitoring processes and reading speed that were related to the types of learner, skilled and failed reader (MORAIS, 1996). The results indicate that the participating students are in reading profile 2 and presented characteristics of the failed reader, once they did not surpass the conditions of the initial reading learning, in the final years of elementary school. The reading comprehension test indicates that Codap / UFS 6th graders presented better results than CEMPP students and that 9th grade students from both schools did not follow development in reading comprehension according to the years of schooling. The statistical significance test was performed to correlate the performance results in both tests. Student t-test showed that the automaticity processes measured in oral reading fluency are predictors of reading comprehension. Thus, our hypothesis that automaticity in the process of decoding the reading is necessary for the comprehension of the text was confirmed._________________________________________________________________________________________